Recalling Cohnheim's theory: papillary renal cell tumor as a model of tumorigenesis from impaired embryonal differentiation to malignant tumors in adults - Banyai, Daniel; Kovacs, Gyula (International journal of biological sciences, 2018)
We have suggested that papillary renal cell tumor (PRCT) of the kidney arises from nephrogenic rest-like lesions. To approve our hypothesis, we worked up 14 kidneys bearing papillary and 14 ones with conventional renal cell carcinoma (CRCC) histologically and found 42 papillary lesions in average per kidney bearing PRCT. PRCTs are characterized by loss of the Y chromosome and trisomy of chromosomes 7 and 17. The MET and HNF1B are localized to chromosome 7q31 and 17q21 and are frequently amplified in PRCT. We have analyzed the expression of the mutant MET in hereditary PRCTs and precursor lesions and found duplication and expression of the mutated allele. Because both genes are involved in early stage of nephron development, we have analyzed the expression of MET and HNF1B by immunohistochemistry in fetal kidneys, precursor lesions and PRCTs. We detected strong expression of MET and HNF1B in distal compartment of S-shaped body of fetal kidneys and in nephrogenic rest-like precursor lesions. Our finding suggests an association between expression of MET and HNF1B in precursor lesions and development of PRCT. We propose a model involving chromosomal clonal evolution and corresponding gene expression for development of PRCTs from embryonic rests due to impaired differentiation. Our model suggests that PRCT have a natural history distinct from that of most common CRCC.